The Sámi world
1 online resource.
Keywords: "This book provides a comprehensive and multifaceted analysis of the Sámi society and its histories and people, offering valuable insights into how they live and see the world. The chapters examine a variety of social and cultural practices and consideration is given to environment, legal and political conditions and power relations. The contributions by a range of Sámi specialists and Indigenous scholars are drawn from across the Sápmi region, which spans from central Norway and central Sweden across Finnish Lapland to the Kola Peninsula in Russia. Sámi perspectives, concepts and ways of knowing are foregrounded throughout the volume. The material connects with wider discussions within Indigenous studies and engages with current concerns relating to globalization, environmental and cultural change, Arctic politics, multiculturalism, postcolonialism and neoliberalism. The Sámi World will be of interest to scholars from a number of disciplines, including Indigenous studies, anthropology, sociology, geography, history and political science"--